The Greatest Films Never Seen: The Film Archive and the Copyright Smokescreen - Op den Kamp, Claudy (Framing Film, 2017)
Orphan works, or artworks for which no copyright holder is traceable, pose a growing problem for museums, archives, and other heritage institutions. As they come under more and more pressure to digitize and share their archives, they are often hampered by the uncertain rights status of items in their collections. This book uses the prism of copyright to reconsider human agency and the politics of the archive, and asks what the practical implications are for educational institutions, the creative industries, and the general public.